A Herpes Simplex Virus (HSV)-2 Single-Cycle Candidate Vaccine Deleted in Glycoprotein D Protects Male Mice From Lethal Skin Challenge With Clinical Isolates of HSV-1 and HSV-2. (5th December 2017) - Burn, Clare; Ramsey, Natalie; Garforth, Scott J; Almo, Steven; Jacobs, William R; Herold, Betsy C
Abstract : HSV-2 ΔgD-2, but not adjuvanted, recombinant glycoprotein D, completely protects male mice from challenge with clinical isolates of HSV and prevents the establishment of latency in peripheral nerves. Protection correlates with FcγRIV-activating antibodies that confer passive protection to naive mice. Abstract: Herpes simplex virus (HSV) infections manifest as recurrent oral or genital mucosal lesions, meningoencephalitis, corneal blindness, and perinatal disease. Subunit vaccines have advanced into the clinic without success. None were tested preclinically in male mice. We compared a single-cycle candidate vaccine deleted in HSV-2 glycoprotein D (ΔgD-2) and subunit gD-2 or gD-1 protein vaccines in a male murine skin model. The ΔgD-2 provided complete protection against 10 times the lethal dose of HSV-1 or HSV-2 clinical isolates, and no latent virus was detected, whereas gD-1- and gD-2-adjuvanted proteins provided little or no protection. Protection correlated with Fc receptor activating but not neutralizing antibody titers.